Beneficial Effects of Sideritis clandestina Extracts and Sideridiol against Amyloid β Toxicity - Anna Gioran; Yiorgos Paikopoulos; Eleni Panagiotidou; Aikaterini E. I. Rizou; Georgia I. Nasi; Virginia D. Dimaki; Konstantina D. Vraila; Dimitra S. Bezantakou; Panagiotis M. Spatharas; Nikos C. Papandreou; Vassiliki Magafa; Fotini N. Lamari; et al. (MDPI AG, 2024)
Alzheimer's disease (AD) is the most common form of dementia. Given the link between oxidative stress and AD, many studies focus on the identification of natural antioxidants against AD. Although their antioxidant capacity is important, increasing data suggest that additional activities are related to their beneficial effects, including properties against amyloid beta (Aβ) aggregation. Sideritis spp. (mountain tea) extracts possess not only antioxidant activity but also other bioactivities that confer neuroprotection. Although various Sideritis spp. extracts have been extensively studied, there are scarce data on S. clandestina subsp. peloponnesiaca (SCP) phytochemical composition and neuroprotective potential, while nothing is known of the responsible compounds. Given that SCP is a weaker antioxidant compared to other Sideritis spp., here, we investigated its potential beneficial properties against Aβ aggregation. We characterized different SCP extracts and revealed their anti-aggregation activity by taking advantage of established C. elegans AD models. Importantly, we identified two pure compounds, namely, sideridiol and verbascoside, being responsible for the beneficial effects. Furthermore, we have revealed a potential anti-Aβ aggregation mechanism for sideridiol. Our results support the use of mountain tea in the elderly against dementia and demonstrate the activity of sideridiol against Aβ aggregation that could be exploited for drug development.